Thinking of Children: Analysis of the Notions about Childhood in Chilean Productions - Olivares Espinoza, Barbara Rocío (Revista de Psicología, 2022)
This article presents the information produced from the analysis of secondary sources, mainly 69 scientific articles from the Scielo-Chile and Scopus databases, where the aim is to identify what and how research has been conducted on childhood in Chile, in the period between 2005 and 2019. The proposed exercise seeks to identify and characterise the notions behind the ways of conceptualising children. The selected corpus was subjected to a thematic categorical content analysis, from which central categories such as the notion of subject/object, implications for social intervention, and methodologies used emerge. It is concluded that views on childhood coexist, ranging from placing the child as an object of protection, study and care, to considering him/her as a subject of rights.